Are NGOs the better donors? A case study of aid allocation for Sweden - Axel Dreher; Florian Mölders; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2007)
This paper analyzes whether and to what extent non-governmental organizations (NGOs) outperform official donors by allocating aid in a way that renders effective poverty alleviation more likely. We employ Probit and Tobit models and make use of an exceptionally detailed database that allows an assessment of the allocation of Swedish NGO aid in comparison to the allocation of Swedish official aid. Our results show that NGOs are more selective when deciding about which countries to enter at all. Moreover, in contrast to NGO aid, there is some evidence that political and commercial motives matter for the selection of ODA recipients. However, the Swedish case also supports the skeptical view according to which NGOs are unlikely to outperform official donors by providing better targeted aid when it comes to the allocation across recipients having passed the eligibility test.
Keywords: O11; O19; F35; 330; NGO aid; ODA; Sector-specific aid; Aid allocation; Entwicklungshilfe; Schwedisch; Entwicklungsorganisation; Private Entwicklungshilfe; Armutspolitik; Wirtschaftspolitische Wirkungsanalyse; Vergleich; Schweden; Entwicklungsländer